Southern from scratch : pantry essentials and down-home recipes - English, Ashley, 1976- (Roost Books, an imprint of Shambhala Publications, Inc., 2018)
Build a from-scratch Southern pantry with 50 essential recipes, then discover the versatility and flexibility of cooking from your larder with 100 more recipes for fresh takes on Southern favorites. Learn how to make the most of local ingredients with recipes for pickles and relishes, jams and spreads, sauces and vinegars, and more that use whole, natural, and in-season produce. With these flavorful bases and embellishments on hand, Ashley English opens up a world of Southern cuisine by sharing ideas and recipes that incorporate these classic staples. With recipes ranging from Southern Greens with Chow Chow, Pickled Beet Deviled Eggs, and Succotash to Cornmeal Catfish with Spikey Tartar Sauce, Slow Cooker Barbeque Chicken, and Grit Cakes with Country Ham and Applesauce, this is a warm and down-to-earth homage to Southern Appalachian home cooking.